Cross-Cultural Aesthetics: Integrating Abaya and K-Fashion in Contemporary Muslim Fashion Design - Nabilah Tsuroya Basya; Ahmad Ashfia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Acculturation in fashion arises as a result of globalization, fostering the integration of local and global cultural elements to create a modern style that adheres to Sharia principles. Two prominent forms of fashion that exemplify this cultural acculturation are the abaya and K-fashion. This article seeks to analyze how young Muslim Gen Z navigates the acculturation of abaya and K-fashion, particularly in their adaptation to local culture and Islamic Sharia guidelines. Additionally, the article underscores the necessity for government support for local fashion industry players who blend global trends, such as K-fashion and abaya, with a distinctly local cultural approach. This support may encompass training, financing, and promotion in international markets. Moreover, the article examines the role of globalization in developing a unique identity for Muslim women and its implications for the fashion industry. The research employs a descriptive qualitative methodology with an anthropological lens, utilizing modeling strategies that encompass attention, retention, reproduction, and motivation. Data for this study were collected through interviews, journals, books, and digital communication platforms, including WhatsApp and Instagram. The results demonstrate that preferences in Muslim women's fashion are heavily influenced by exposure to social media (attention), which drives individuals to purchase these fashion products (retention). The diverse options available can be tailored to align with Islamic norms and Sharia principles (reproduction), thus motivating individuals to curate their fashion collections (motivation).